Belonging mediates the relationship between emotional contagion and digital competence among university students - Mohamed Ali Nemt-allah; Ghada Mahros Abdelhafiez; Randa Rabie Abdelbadie; Soma Abdelrazek Elfeshawy; Sara Awadallah Mohammed; Ashraf Ragab Ibrahim (Institute of Advanced Engineering and Science, 2026)
Emotional contagion (EC) significantly influences student experiences in university settings, yet its relationship with digital competence—a key requirement for contemporary academic success—remains unclear. This study examined the mediating role of sense of belonging in the relationship between EC and digital competence among Egyptian university students. Two samples from Al-Azhar University were recruited: a psychometric validation sample (N=486) and a main study sample (N=737). Participants completed validated Arabic versions of the sense of belonging inventory, the susceptibility to emotional contagion (SEC) scale, and the digital competence scale for university students. Data were analyzed using correlation analyses and structural equation modeling (SEM) with bootstrap testing. Results showed that sense of belonging partially mediated relationships between both types of EC and digital competence. Positive EC had significant direct effects on belonging (β=.354) and digital competence (β=.195), with 39.4% of its total effect mediated through belonging. Negative EC also had significant direct effects on belonging (β=-.119) and digital competence (β=-.141), with 23.4% mediated through belonging. These findings suggest that higher education institutions should implement belonging-enhancement initiatives to strengthen digital competence and maximize the benefits of positive EC while mitigating negative emotional influences.